Expanding stroke telerehabilitation services to rural veterans: a qualitative study on patient experiences using the robotic stroke therapy delivery and monitoring system program. (2nd January 2017) - Cherry, Colleen O'Brien; Chumbler, Neale R.; Richards, Kimberly; Huff, Amber; Wu, David; Tilghman, Laura M.; Butler, Andrew
Abstract: Purpose : The present study reports on a robotic stroke therapy delivery and monitoring system intervention. The aims of this pilot implementation project were to determine participants' general impressions about the benefits and barriers of using robotic therapy devices for in-home rehabilitation. Methods : We used a qualitative study design employing ethnographic-based anthropological methods including direct observation of the in-home environment and in-depth semi-structured interviews with 10 users of the hand or foot robotic devices. Thematic analysis was conducted using an inductive approach. Results : Participants reported positive experiences with the robotic stroke therapy delivery and monitoring system. Benefits included convenience, self-reported increased mobility, improved mood and an outlet for physical and mental tension and anxiety. Barriers to use were few and included difficulties with placing the device on the body, bulkiness of the monitor and modem connection problems. Conclusions : Telerehabilitation robotic devices can be used as a tool to extend effective, evidence-based and specialized rehabilitation services for upper and lower limb rehabilitation to rural Veterans with poor access to care. Implications for Rehabilitation: Participants whose formal therapy services had ended either because they had exhausted their benefits or because traveling to outpatient therapy was too cumbersome due to distance were able to perform therapeutic activities in the home daily (or at least multiple times per week). Participants who were still receiving formal therapy services either in-home or in the clinic were able to perform therapeutic activities in the home on the days they were not attending/receiving formal therapy. Based on the feedback from these veterans and their caregivers, the manufacturing company is working on modifying the devices to be less cumbersome and more user-friendly (lighter-weight, more mobile, changing software, etc.), as well as more adaptable to participants' homes. Removing these specific barriers will potentially allow participants to utilize the device more easily and more frequently. Since participants expressed that they wished they could have the device in their homes longer than the 3-month usage period required for this pilot project, the project team is working on a proposal to extend this project to a wider area and the new paradigm would extend the usage period until the patient reaches a plateau in progress or no longer wants to use the device.